Industrial relations practice in Nigeria: issues and perspectives (2022)
The study relied on the documentary method and obtained secondary sources data from a review of journals, textbooks, and official publications to examine the impacts of these two eras on industrial relations practice by diagnosing their involvement, intervention, and interference in labour union movements in the country. As the largest employer of labour, the government was more than the employer in the power dynamics of industrial relations practice. The industrial relations System evolved in an environment of government involvement, intervention, and interference, whether it was the military or civilian government in power. Consequently, the industrial relations practice in Nigeria has not been able to represent the management of institutionalized relationships in the social System to promote harmonious industrial co-existence between principal actors: government and labour unions. The study suggested that the government should serve as regulators in the industrial relations Systems to manage institutionalized relationships through policies and evolve self-governing mechanisms devoid of interference for harmonious mutual co-existence with labour unions for stability in the policy and economic posterity in Nigeria